Cardiovascular Effects of Long‐Term Exposure to Air Pollution: A Population‐Based Study With 900 845 Person‐Years of Follow‐up. Issue 11 (8th November 2017) - Kim, Hyeanji; Kim, Joonghee; Kim, Sunhwa; Kang, Si‐Hyuck; Kim, Hee‐Jun; Kim, Ho; Heo, Jongbae; Yi, Seung‐Muk; Kim, Kyuseok; Youn, Tae‐Jin; Chae, In‐Ho
Abstract : Background: Studies have shown that long‐term exposure to air pollution such as fine particulate matter (≤2.5 μm in aerodynamic diameter [PM2.5 ]) increases the risk of all‐cause and cardiovascular mortality. To date, however, there are limited data on the impact of air pollution on specific cardiovascular diseases. This study aimed to evaluate cardiovascular effects of long‐term exposure to air pollution among residents of Seoul, Korea. Methods and Results: Healthy participants with no previous history of cardiovascular disease were evaluated between 2007 and 2013. Exposure to air pollutants was estimated by linking the location of outdoor monitors to the ZIP code of each participant's residence. Crude and adjusted analyses were performed using Cox regression models to evaluate the risk for composite cardiovascular events including cardiovascular mortality, acute myocardial infarction, congestive heart failure, and stroke. A total of 136 094 participants were followed for a median of 7.0 years (900 845 person‐years). The risk of major cardiovascular events increased with higher mean concentrations of PM2.5 in a linear relationship, with a hazard ratio of 1.36 (95% confidence interval, 1.29–1.43) per 1 μg/m 3 PM2.5 . Other pollutants including PM2.5–10 of CO, SO2, and NO2, but not O3, were significantly associated with increased risk of cardiovascular events. The burden from air pollution was comparable to that from hypertension and diabetes mellitus. Conclusions: This large‐scale population‐based study demonstrated that long‐term exposure to air pollution including PM2.5 increases the risk of major cardiovascular disease and mortality. Air pollution should be considered an important modifiable environmental cardiovascular risk factor.